2009
DOI: 10.3892/or_00000648
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin induces apoptosis in human lung adenocarcinoma A549 cells through a reactive oxygen species-dependent mitochondrial signaling pathway

Abstract: Abstract.Several studies have shown that curcumin can induce apoptosis and inhibit growth in human A549 lung adenocarcinoma cells. However, the mechanism is not completely understood yet. The present study was designed to investigate the effects of curcumin on A549 cells to better understand its apoptosis and apoptosis-related factors in vitro. The apoptosis induction, intracellular reactive oxygen species (ROS) and mitochondrial membrane potential (MMP) were examined by confocal fluorescence microscope and fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 27 publications
3
52
0
3
Order By: Relevance
“…There are numerous reports about the production of reactive oxygen species (ROS) as one of the first steps in curcumin cytotoxicity to different tumor cell lines (Atsumi et al, 2005;Chen et al, 2010;Fujisawa S, 2004;Hail, 2008;Kang et al, 2005). We also detected ROS formation quite early after curcumin was added and found more ROS in parental HEp-2 cells.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…There are numerous reports about the production of reactive oxygen species (ROS) as one of the first steps in curcumin cytotoxicity to different tumor cell lines (Atsumi et al, 2005;Chen et al, 2010;Fujisawa S, 2004;Hail, 2008;Kang et al, 2005). We also detected ROS formation quite early after curcumin was added and found more ROS in parental HEp-2 cells.…”
Section: Discussionmentioning
confidence: 56%
“…There are numerous reports about ROS involvement in curcumin induced apoptosis in the literature (Atsumi et al, 2005;Chen et al, 2010;Fujisawa S, 2004;Hail, 2008;Kang et al, 2005). Apoptosis inhibition was found to be one of the causes of resistance to curcumin in some cell lines (Karunagaran et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cur has been shown to enhance monokaryon phagocytosis by macrophages, increase immune regulation, inhibit the proliferation, and induce apoptosis of immortal cell lines such as HL-60, K-562, MCF-7, HOS, and VSM cells (Dubey et al, 2008;Hussain et al, 2008;Miller et al, 2008;Lee et al, 2009;Chen et al, 2010a;2010b;Giommarelli et al, 2010;Watson et al, 2010). In our previous studies, we found that Cur effectively inhibited LEC proliferation, and that Cur increased the concentrations of intracellular Ca 2+ and cyclic adenosine monophosphate and decreased the concentration of cyclic guanosine monophosphate in LECs (Hu et al, 2006a;2006b).…”
Section: Introductionmentioning
confidence: 99%